Viscosity as a key factor in decision making of nectar feeding ants. (January 2021) - Lois-Milevicich, Jimena; Schilman, Pablo E.; Josens, Roxana
Graphical abstract: Highlights: Ants fed sucrose solutions whose viscosity was increased by the addition of tylose. This increase of only the viscosity raised antś metabolic rate during feeding. The volume per pump contraction varied with viscosity but not with concentration. A low concentration and increased viscosity caused a fast decrease in pump frequency. Ants could rapidly integrate information from different food properties while feeding. Abstract: It is well known that viscosity reduces the intake rates in nectar-feeding insects, such as nectivorous ants, though it remains unclear whether viscosity imposes a higher energy investment in these insects, and how this affects their feeding motivation. To address this issue, we studied feeding behavior, metabolism, and pharyngeal pump activity in the carpenter ant Camponotus mus during ingestion of ad libitum sucrose solutions. In some solutions tylose was added to modify viscosity without changing its sucrose concentration, in a way that allowed comparing: (1) two solutions with the same viscosity and different sucrose concentration (10 T and 50), and (2) two solutions with different viscosity and the same sucrose concentration (50 and 50 T). The viscosity increase was detrimental to the metabolic rate and energy balance. Ants feeding on a solution with high sucrose concentration and increased viscosity (50 T) spent extra-time until reaching a crop load similar to that reached by ingesting the solution without tylose (50). For all solutions offered, ants started feeding with the same pharyngeal pump frequencies, reflecting a similar motivation. Interesting, when ants fed on a low sucrose concentration and increased viscosity solution (10 T), their pump frequencies dropped rapidly respect to the pure-sucrose solution (50). On the contrary, pump frequencies for 50 and 50 T remained similar until the end of the intake. Since the pump frequency is strongly modulated by the ant motivation, an increase in viscosity with low sucrose content, demotivates the ants rapidly, suggesting a rapid integration of different kinds of information about the food value. Our results helped to understand how nectivorous ants could modulate their foraging decision-making.